Les marchands latins dans les ports musulmans méditerranéens : une minorité confinée dans des espaces communautaires ? - Dominique Valérian (Revue des Mondes Musulmans et de la Méditerranée)
Since the twelfth century, European merchants used to live in Muslim ports, but spaces actually frequented by them seem to be relatively limited to certain places strictly controlled. Even if peace agreements let them free to go and trade wherever they wanted, documents show them mostly in their fondaco, where they can organise themselves according to the rules of their homeland. Contacts with local actors took place first inside custom and toll collecting bureaus, under the control of Muslim officers. However, in spite of that spatial segregation organised by Muslim ruler and European consuls, those who lived there for longer periods could also trade freely and directly in the suqs and frequent the rest of the town.